2012
DOI: 10.2166/wpt.2012.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of precipitation and external carbon source addition on biological nutrient removal in activated sludge systems – experimental investigation and mathematical modeling

Abstract: The aim of this study was to determine the effects of chemical precipitation and addition of external carbon sources on the denitrification capability and enhanced biological phosphorus removal (EBPR) interactions at the ‘Wschod’ WWTP (600,000 PE) in Gdansk (northern Poland). For this purpose, different kinds of batch experiments were carried out with the settled wastewater (without pretreatment and after coagulation-flocculation) and external carbon sources (ethanol and fusel oil). Precipitation of colloidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This approach drew on the concept, suggested Maruéjouls et al [47], that PSVD is a determining factor for the prediction of the wastewater quality along a catchment, a combined sewer, or a primary treatment system. This research, as well as studies conducted by other authors [47,[51][52][53][54][55]57], confirms that a comparative study of the original and modified ASM2d models that accounts the effects of the COD fraction and particles sizes of molecules on the hydrolysis process should be applied under transient conditions (summer, spring and winter). The distribution data were fed into the hydrolysis model that involved a comparison of results on the wastewater quality that were obtained in the course of simulations that were performed at the hydrolysis rates of particles (such as molecules size and forms of COD substrates) that depended on the OUR batch tests as well as the conditions of the settling velocities ( Figure 5).…”
Section: Modelling Hydrolysis Rate Vs Settling Velocity Of the Cod Fosupporting
confidence: 83%
See 1 more Smart Citation
“…This approach drew on the concept, suggested Maruéjouls et al [47], that PSVD is a determining factor for the prediction of the wastewater quality along a catchment, a combined sewer, or a primary treatment system. This research, as well as studies conducted by other authors [47,[51][52][53][54][55]57], confirms that a comparative study of the original and modified ASM2d models that accounts the effects of the COD fraction and particles sizes of molecules on the hydrolysis process should be applied under transient conditions (summer, spring and winter). The distribution data were fed into the hydrolysis model that involved a comparison of results on the wastewater quality that were obtained in the course of simulations that were performed at the hydrolysis rates of particles (such as molecules size and forms of COD substrates) that depended on the OUR batch tests as well as the conditions of the settling velocities ( Figure 5).…”
Section: Modelling Hydrolysis Rate Vs Settling Velocity Of the Cod Fosupporting
confidence: 83%
“…The goal of the presented research was to show the potential of these particulate forms of COD in order to better describe the hydrolysis that occurs in the course of the wastewater treatment bioprocesses (e.g., pre-denitrification and denitrification-nitrification) in an activated sludge system and to better predict the quality of the WWTP effluent. This paper compared the calibration and validation of the original and modified ASM2d models by using experimental data that were obtained by conducting respirometric OUR tests on wastewater samples that were fractionated by different sizes of COD molecules and their forms, as well as from studies conducted by the authors [26,[51][52][53][54][55]. For example, the experiments that were performed in [56] showed that when wastewater flows from an urban catchment to the biological treatment, the particle settling velocity distribution (PSVD) becomes highly differentiated.…”
Section: Modelling Hydrolysis Rate Vs Settling Velocity Of the Cod Fomentioning
confidence: 99%
“…Though the enhanced chemical pre-treatment step can reduce total phosphorus in the BAF influent, removal of considerable amount of organic matters would also be resulted meanwhile (Rogalla et al, 1990). The simultaneous organic matter removal in the chemical pre-treatment step may lead to shortage of carbon sources in the subsequent biological nitrogen removal process and hence result in reduced denitrification efficiency (Makinia et al, 2012), particularly when treating weak domestic wastewater with relatively low C/N ratio. For compensating the loss of carbon source, the addition of external carbon sources in the denitrification process are often required, and therefore operation cost increases.…”
Section: Introductionmentioning
confidence: 99%
“…[1] In these circumstances, effective use of biodegradable substrates as an internal carbon sources for denitrification and enhanced biological phosphorus removal as well as optimizing the performance of aeration systems in bioreactors, may be useful for saving energy at WWTPs. [2][3][4] In this situation, the aeration control in the bioreactors is very important, because it is one of the most energy-consuming processes in the wastewater treatment. [5] The energy consumption in the aeration systems usually ranged 50% to 90% of the total electricity consumed by the WWTP (depending on size and technological solutions of plant), which corresponds to 15-40% of the total costs in the wastewater treatment budget.…”
Section: Introductionmentioning
confidence: 99%